Profitabilitas, Aktivitas, dan Solvabilitas Sebagai Determinan dari P/E Ratio: Kajian Empiris di Indonesia - Averio, Thomas (Forum Kerjasama Pendidikan Tinggi, 2025)
Financial performance plays a pivotal role in assessing a company’s overall condition and serves as a critical indicator of its value. This study aims to empirically examine the impact of financial performance on the price-to-earnings (P/E) ratio. In this study, financial performance is examined through three main financial ratios: the profitability ratio proxied by the net profit margin (NPM), the activity ratio proxied by the total asset turnover (TATO), and the solvency ratio proxied by the debt to equity ratio (DER).. The research focuses on firms in the non-cyclical consumer sector listed on the Indonesia Stock Exchange (IDX) during the 2017–2021 period. Multiple linear regression analysis is employed to evaluate the effect of each financial ratio on the P/E ratio. The findings of this study indicate that the profitability ratio, proxied by the net profit margin (NPM), and the activity ratio, proxied by the total asset turnover (TATO), have a significant positive effect on the price-to-earnings (P/E) ratio. Their respective significance values are 0.000 and 0.000, with regression coefficients of 20.532 and 4.548. In contrast, the solvency ratio, proxied by the debt to equity ratio (DER), is found to have an insignificant effect on the P/E ratio, with a significance value of 0.875 and a regression coefficient of 0.007. These findings emphasize that financial performance—particularly profitability and activity—plays a crucial role for investors and the market in evaluating firm value within the Indonesian non-cyclical consumer industry.